A Note on Gödel-Dummet Logic LC - Robles, Gemma; Méndez, José M. (Bulletin of the Section of Logic, 2021)
Let \(A_{0},A_{1},...,A_{n}\) be (possibly) distintict wffs, \(n\) being an odd number equal to or greater than 1. Intuitionistic Propositional Logic IPC plus the axiom \((A_{0}→ A_{1})\vee ...\vee (A_{n-1}→ A_{n})\vee (A_{n}→ A_{0})\) is equivalent to Gödel-Dummett logic LC. However, if \(n\) is an even number equal to or greater than 2, IPC plus the said axiom is a sublogic of LC.